Insights into the role of androgen receptor in human testicular peritubular cells. (5th June 2018) - Mayer, C.; Adam, M.; Walenta, L.; Schmid, N.; Heikelä, H.; Schubert, K.; Flenkenthaler, F.; Dietrich, K.‐G.; Gruschka, S.; Arnold, G. J.; Fröhlich, T.; Schwarzer, J. U.; et al.
Summary: Contractile smooth muscle‐like peritubular cells build the wall of seminiferous tubules in men. They are crucial for sperm transport and complement the functions of Sertoli cells by secreting factors, including glial cell line‐derived neurotrophic factor. Previous studies revealed that they also secrete the chemokine C‐X‐C motif chemokine ligand 12 (CXCL12), which has known roles in spermatogenesis. Peritubular cells express the androgen receptor (AR), which is retained in isolated human testicular peritubular cells. We aimed to explore AR‐regulated functions in human testicular peritubular cells. Bearing in mind that infertile men often have high aromatase activity, which may lower intratesticular androgen concentrations, an animal model for male infertility was studied. These mice display an age‐dependent loss in spermatogenesis due to high aromatase activity. Human testicular peritubular cells were exposed to dihydrotestosterone or the antiandrogen flutamide. We studied AR, smooth muscle cell markers, glial cell line‐derived neurotrophic factor and 15 secreted factors previously identified, including CXCL12. We used qPCR, Western blotting, ELISA or selected reaction monitoring (SRM). In the animal model for male infertility, we employed qPCR and immunohistochemistry. Dihydrotestosterone increased AR and flutamide prevented these actions. The smooth muscle cell markers calponin and smooth muscle actin were likewise increased, while cell size or cellular proliferation was not changed. Dihydrotestosterone did not increase glial cell line‐derived neurotrophic factor or CXCL12 secretion but increased levels of serine proteinase inhibitor (SERPIN) E1. The animal model for male infertility with high aromatase activity showed reduced numbers of AR‐immunoreactive testicular peritubular cells, suggesting that altered androgen and/or oestrogen levels could influence AR‐mediated responses in peritubular cells. Androgens act on human testicular peritubular cells to enhance AR levels, their contractile phenotype and to modulate the secretion of some secreted factors. This study suggests that some aspects of human peritubular cell functions are regulated by androgens.